El uso de las normas internacionales de información financiera como instrumentos de interpretación de la ley del impuesto a la renta peruano - Bejarano Pérez, Henry Pierre (2017)
The thesis analyzes the legality of the use of International Financial Reporting Standards (IFRS) by SUNAT, the Tax Court and the Judiciary as instruments for interpreting concepts insufficiently determined in the Income Tax Law. It realizes that both standards have different purposes and that IFRS do not comply with the constitutional tax parameters. Despite this, the majority position supports its use in the determination of corporate income tax. When analyzing the sources of Tax Law, International Financial Reporting Standards (IFRS) and its relationship with Peruvian corporate income tax, it is identified that our system of determination of the corporate income tax is of double balance or independent balance. In spite, the production of the legal operators evidences problems to considered the accounting how taxable base of the tax, which corresponds to another system, the single balance.